Frequência e distribuição dos sorotipos da dengue circulantes no estado de Sergipe no primeiro semestre de 2016 - Café, Lilian Pinheiro (2016)
The diagnosis of dengue cases in Central Laboratories of Public Health (LACEN) of the country includes the research of NS1 protein and only in positive cases, diagnostic confirmation occurs by identifying the serotype. Data provided by the Epidemiological Surveillance of Sergipe revealed that the first half of 2016 all suspected cases that reached the LACEN / SE were negative on screening tests, even in the thirty-first epidemiological week of the same year, Sergipe has reached the seventh place in the racking of dengue cases in the Northeast region and the third in the Quick Survey Infestation Index by Aedes aegypti. This study aimed to identify the serotypes and the epidemiological profile of suspected dengue cases in the first half of 2016. The 437 suspected dengue patients from January to June of this year were registered in LACEN / SE. After exclusion criteria, 382 serum samples of these patients diagnosed and negative for dengue by ELISA NS1 Antigen Platelia kit method were analyzed by RT-PCR in real time on the multiplex system for confirmation of suspected cases of dengue. The distribution of patients according to epidemiological and demographic variables revealed that there was a predominance of cases in the south central region of the state and large Aracaju (53.5%) inferring the ease in access to outpatient and laboratory service in the region the most affected gender was female (62.8%) and the age group of highest incidence was 20-59 years (59.3%). The highest rate was in urban areas (84.9%) and the first three days of symptoms (63.9%) with higher sampling rate. The prevalence of dengue in cases initially presented as a suspect was 22.5% (86) distributed among serotypes DENV4 82.5% (71), DENV1 9.3% (8) and DENV3 8.1% (7). Compared to official data reported that there were no cases of dengue in the period, this study reveals the positive for dengue with cocirculation of three distinct serotypes being DEV4 the predominant. As also, reports the first evidence of the last ten years of DENV3 serotype circulating in the state. Data analysis enabled to view an underreporting of cases screened and thus suggest a reassessment of the methods used as diagnostic screening so that they can take control measures to the potential for severe disease in a population.